2022
DOI: 10.1371/journal.pone.0273052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of depression, anxiety and stress among frontline healthcare workers at COVID-19 isolation sites in Gaborone, Botswana

Abstract: Introduction Coronavirus disease 2019 (COVID-19) has been associated with mental health outcomes and healthcare workers (HCWs) are at the highest risk. The aim of this study was to determine the prevalence and predictors of depression, anxiety and stress, among frontline HCWs at COVID-19 isolation and treatment sites in Gaborone, Botswana. Methods This was a cross-sectional study using self-administered questionnaires at the six (6) isolation facilities. The 42-item Depression, Anxiety and Stress Scale (DASS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Another review showed that social stigma was a predisposing risk factor for the development of burnout among intensive care nurses during the COVID-19 pandemic [38]. Other studies also showed a significant association between stigma and depression, anxiety and psychological distress in COVID-19 HCWs [24,25,39]. Poor mental wellbeing negatively impacts job performance and therewith quality of care [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Another review showed that social stigma was a predisposing risk factor for the development of burnout among intensive care nurses during the COVID-19 pandemic [38]. Other studies also showed a significant association between stigma and depression, anxiety and psychological distress in COVID-19 HCWs [24,25,39]. Poor mental wellbeing negatively impacts job performance and therewith quality of care [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…According to Shah J et al, onehalf of HCWs (53.6%) in Kenya tested positive for depression, with the majority suffering from moderate depression (8). Further studies undertaken among HCWs in Botswana, Uganda, and Sudan using the DASS-21, found 21%, 40.3% and 75% prevalence of depression, respectively (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%